1993
DOI: 10.2307/1591449
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virulent Hemorrhagic Enteritis Virus for the Induction of Colibacillosis in Turkeys

Abstract: Three hundred fifty 1-day-old large white turkeys were reared in brooding batteries to 10 days of age, after which they were moved to floor pens on litter. At 7 weeks of age, poults were allotted into four treatment groups as follows: 1) virulent hemorrhagic enteritis virus (HEV) alone (100 turkeys), 2) Escherichia coli alone (100 turkeys), 3) HEV + E. coli (100 turkeys), and 4) negative controls (50 turkeys). HEV was given orally at 7 weeks of age, followed by E. coli challenge in the drinking water 2 days la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…These findings are significant because of the low-virulence of the HE virus used in the experiment and that the infections with this virus in the field caused no clinical signs while post-mortem examination revealed only the enlargement and marble-like appearance of the spleen which is typical for the infection with the HE virus. The findings of this study are similar to those of other authors (Sponenberg et al 1985, Newberry et al 1993, van den Hurk et al 1994, Pierson et al 1996.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are significant because of the low-virulence of the HE virus used in the experiment and that the infections with this virus in the field caused no clinical signs while post-mortem examination revealed only the enlargement and marble-like appearance of the spleen which is typical for the infection with the HE virus. The findings of this study are similar to those of other authors (Sponenberg et al 1985, Newberry et al 1993, van den Hurk et al 1994, Pierson et al 1996.…”
Section: Discussionsupporting
confidence: 93%
“…This is caused by different virulence factors of APEC, host susceptibility to infection as well as resistance factors (environmental toxins, immunity, nutrition) (Barnes et al 2003). Infections with the haemorrhagic enteritis virus (HEV) are a frequent factor which makes turkeys more susceptible to infections with the APEC and the development of the clinical form of colibacillosis (Newberry et al 1993, van den Hurk et al 1994, Pierson et al 1996. The quoted authors conducted their studies both under laboratory conditions and in the field, on turkeys infected with the HEV of different virulence levels.…”
Section: Introductionmentioning
confidence: 99%
“…coli patogênica para aves (APEC), também pode ter origem intestinal, e nessa forma comumente se visualiza hepatite e esplenite fibrinonecróticas, que pode se disseminar para diversos órgãos (Newberry et al 1993. A maioria das aves condenadas por colibacilose apresentaram apenas lesões hepáticas, o que pode sugerir uma origem bacteriana intestinal.…”
Section: Discussionunclassified
“…This intestinal damage is important because of its involvement with septicaemic colibacillosis. Investigators (Larsen et al, 1985;Newberry et al, 1993) have reported that E. coli septicaemia may be induced by HEV. Previous research has shown that mortality is extremely difficult to induce in turkeys kept in isolators even when using doses of virus that kill birds kept on litter (personal data).…”
Section: Discussionmentioning
confidence: 99%
“…MSDV is a group II avian adenovirus which is used in turkeys as a vaccine because of its ability to induce immunity to HEV. HEV is also a group II avian adenovirus which can cause a disease characterized by severe enteritis, bloody droppings and death, and can also initiate colibacillosis (Larsen et al, 1985;Newberry et al, 1993). Typically, this disease occurs in poults 4 weeks of age or older (Domermuth and Gross, 1991).…”
Section: Introductionmentioning
confidence: 99%